Currency substitution, financial innovations and money demand - Matti Virén (Bank of Finland, 1989)
This paper presents some Finnish evidence on the importance of currency substitution and financial innovations for money demand. It is also shown that conventional demand for money specifications which do not take these factors into account are clearly misspecified and produce unreasonable results. The problem is particularly acute for narrow concepts of money.
URN:NBN:fi:bof-201807301762
Keywords: 330